Impact Evaluation Of The Road Infrastructure Development Policy In Improving The Quality Of Education Services In Indonesia - Aji Primanto; Gunawan Undang (Jurnal Mantik, 2022)
Impact evaluation is to determine the impact of policy implementation that has been carried out by policy implementers. According to Patton, Sawicki, Clark, the method that can be used to measure the success of the performance of the impact of the policy is before and after comparison. This research uses a literature study method through analysis of data obtained from BPS, Ministry of PUPR, and Ministry of Finance. The results show that the impact of road infrastructure development policies has not been in accordance with the national development mission. Before the government increased the budget for infrastructure improvements in 2010-2014, the number of high school students who did not continue their studies to higher education at that time was 39.06%).